Construction of three-dimensional net-like polyelectrolyte multilayered nanostructures onto titanium substrates for combined antibacterial and antioxidant applications. Issue 32 (6th August 2018) - Sutrisno, Linawati; Wang, Sixiang; Li, Menghuan; Luo, Zhong; Wang, Chunli; Shen, Tingting; Chen, Peixing; Yang, Li; Hu, Yan; Cai, Kaiyong
Abstract : Fabrication of nanofibers and a bacteria-triggered antibiotic-releasing coating to modify titanium substrates for antibacterial and antioxidant applications. Abstract : Bacterial biofilm formation and oxidative stress induced by the production of reactive oxygen species (ROS) are major causes of implant failure. An emerging approach to overcome these issues is to combine chitosan–polycaprolactone (PCL) nanofibers and polyelectrolyte multilayers composed of tannic acid (TA) and gentamicin sulfate (GS) for the localized co-delivery of antioxidants and antibiotics from the titanium surface. The integration of nanofibers (NFs) and layer-by-layer (LBL) technology could provide a larger surface area and thus increase the number of cationic sites of Ti substrates. The coating of NF substrates with TA/GS resulted in higher ( p < 0.05 or p < 0.01) cellular activities than those of Ti substrates, including enhanced proliferation and gene expression. Furthermore, in vitro investigation demonstrated that TA/GS-incorporated Ti-polydopamine (PDA)/NF implants exhibited excellent stability, and antibacterial and antioxidant properties. The results showed that Ti-PDA/NF/LBL substrates have a biodegradable character in vivo . All the results indicated that the combination of NFs and the bacteria-triggered antibiotic-releasing coating could be used for the tailored co-delivery of antibacterial and antioxidant agents from various metallic implantable devices to effectively improve early bone healing even under ROS stress and decrease the risk of biofilm-associated infections in patients.